Neves-corvo 3D - A high-resolution seismic survey at a mine camp scale - Ziramov, Sasha; Kinkela, J.; Urosevic, Milovan (2016)
Four consecutive 3D seismic surveys were acquired across the Neves Corvo mining camp in Portugal over a period of two years. The first survey undertaken was in 2011 over the known Semblana deposit, which proved that the 3D seismic method was capable of producing a very clear image of a complex underground orebody at this site. The main objective of the subsequent seismic surveys was the definition of the main structures, which were controlling mineralisation. Initial processing of the seismic data showed great promise in resolving the complex structural environment and also hinted at the possibility for direct targeting from seismic data. However, the quality across four different surveys was highly variable due to different acquisition geometry and source parameters. Moreover, initial processing did not involve preserved relative amplitude processing, which was key for the direct targeting of ore shoots. After successful application of surface consistent amplitude compensation, it turned out that pre-conditioning in the offset planes, followed by exclusion of unsuccessfully imaged events prior to stacking, produced the highest quality fully merged PSTM seismic cube. This cube could then be used for direct targeting with much more certainty than with any other processing result produced before.